(untitled) (Dhaka University Journal of Science, 2020)
Leucas aspera plant was subjected to isolation of secondary metabolites and screening of their biological activities. Four compounds, stigmasterol, lupeol, β-sitosterol and menthol, were isolated from methanol extract. Sixteen different micro-organisms were used for investigating antimicrobial activity of the different extracts of L. aspera where noteworthy zone of inhibition was observed against Gram positive B. subtilis and S. aureus, B. megaterium and Gram negative S. paratyphi, S. typhi, V. mimicus, S. dysenteriae and V. cholera. In brine shrimp lethality bioassay, the highest lethality was showed by crude methanol extract having LC50 values of 4.07μg/mL. The total antioxidant capacity of crude methanol fraction was found to be 59.40 mg/g of plant extract which was maximum comparing with other fractions. No significant cytotoxicity was observed on both HeLa and Vero cell at 1mg/mL sample inhibition. Dhaka Univ. J. Sci. 68(1): 101-104, 2020 (January)